Case study: Universal service policies and its impact on universal service projects quantity and quality in Egypt - Nader El hussieny; Heba Ibrahim Gharib; Mohab Ibrahim Khamis (International Telecommunications Society (ITS), 2019)
The mobile market has experienced a huge surge in growth across the globe. However, mobile network operators are still struggling to extend coverage to rural areas. Universal Service would appear to be an emerging concept; the reason for this is that Universal Service aims to support the telecom rural connectivity therefore increases the competition. The expanding interest in extending the mobile coverage to rural areas has promoted the advancement in the elaboration of universal services policies and mechanisms. Universal service policies tend to focus on projects selection criteria mechanisms and funding mechanisms to achieve the policy goals. In this paper, we proposed universal service mechanisms able to optimize and enhance the universal service project quantity and quality in terms of: 1) coverage area, 2) network growth and 3) BTS average cost, 4) Planned time, and 5) Technology used in order to connect the underserved and rural areas in an effective and efficient manner. This paper does not intend to deal extensively with all the relevant aspects of Universal Service, but seeks primarily a regulatory/policy approach. The paper starts by formulating the definition of Universal Service and outlining the changes in the concept of Universal Service from a policy and regulatory perspective. The paper reveals that connecting remote and rural regions has presented tough challenges for the telecom industry. The paper then looks into the possibilities for further developing Universal Service policies. Then the paper discusses universal service projects quantity and quality factors. The paper also discusses the different aspects of projects quality, as projects tend to follow the triple constraint: scope, schedule, and budget. The paper also discusses thoroughly how to measure the projects quality. The paper will measure the quality and quantity of universal service projects before and after updating the universal service policy to compare between both results and to prove that the updated universal service policy has an impact on the number of projects and the quality of them and by applying and developing the different concepts of universal service policies, the quantity and quality of US projects will be improved and enhanced.
Keywords: 330; universal Service; universal service policies; mobile coverage; projects quality; universal service projects; rural areas